Perceptions of Effective English Teachers and Lecturers: Voices of Pre-Service English Teachers in an Indonesian EFL Context - Bukhori Bukhori; Zelly Putriani; Cut Raudhatul Miski; Dedy Wahyudi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Understanding what constitutes an effective English teacher or lecturer is essential for shaping competent future educators, particularly in EFL (English as a Foreign Language) contexts like Indonesia. However, limited research explores how pre-service English teachers perceive the effectiveness of both school-level teachers and university lecturers. This study employed a quantitative survey design involving 102 fifth-semester students from the English Education Department of an Indonesian university. Data were collected through a validated questionnaire comprising 60 items across four domains: organizational and communication skills, pedagogical knowledge, socio-affective skills, and English proficiency. Descriptive statistics were used to analyze responses. Findings revealed that pre-service teachers perceived both English teachers and lecturers as sharing similar core characteristics. Effective teachers were associated with stimulating interaction, clear lesson planning, and motivating learners. Effective lecturers were more strongly associated with using clear and simple language, demonstrating vocabulary mastery, and providing constructive feedback. Fairness, patience, and supportive attitudes were highly valued for both roles, while excessive focus on error correction was considered less important. The study underscores the importance of pedagogical clarity, interpersonal sensitivity, and language proficiency in English teaching across educational levels. It also highlights nuanced differences in role expectations between teachers and lecturers. These findings offer valuable insights for English teacher education programs to balance content knowledge, instructional skills, and relational competence.